A study of starch gelatinisation behaviour in hydrothermally-processed plant food tissues and implications for in vitro digestibility. Issue 12 (9th September 2015) - Edwards, Cathrina H.; Warren, Frederick J.; Campbell, Grant M.; Gaisford, Simon; Royall, Paul G.; Butterworth, Peter J.; Ellis, Peter R.
Abstract : Within plant tissues of different particle sizes, the extent of gelatinisation revealed by DSC was related to the in vitro digestion of encapsulated starch granules. Abstract : The aim of this study was to investigate the role of the plant food matrix in influencing the extent of starch gelatinisation during hydrothermal processing, and its implications for starch digestibility. Differential scanning calorimetry (DSC) was used to provide a detailed examination of the gelatinisation behaviour of five distinct size fractions (diameters <0.21 to 2.58 mm) of milled chickpea and durum wheat. Gelatinisation parameters were obtained from the DSC thermograms and concomitant microscopy analyses were performed. The estimated terminal extent of gelatinisation (TEG) was compared with our previously published data for in vitro starch digestibility of the same food materials. We observed clear differences in the gelatinisation behaviour of matched size-fractions of chickpeas and durum wheat. In chickpea materials, the TEG values (34–100%) were inversely related to particle size, whereas in durum wheat, no size-dependent limitations on TEG were observed. The TEG values were completely consistent with the extent of starch amylolysis in all size fractions of both durum wheat and chickpea. Microstructural analysis following hydrothermal processing confirmed the presence of some partially gelatinised birefringent starch within intact chickpea cells. Birefringent starch granules were not present in any of the processed fractions of durum wheat. The differences in gelatinisation behaviour of these plant species seem to reflect the individual cell wall properties of these materials. These findings demonstrate the applicability of DSC to real food materials to provide insight into the mechanisms by which the food matrix (particularly the plant cell walls) influences gelatinisation, and consequently, starch amylolysis.